Certificateless-based efficient aggregate signature scheme with universal designated verifier - Yu-lei ZHANG; Dong-rui ZHOU; Chen-yi LI; Yong-jie ZHANG; Cai-fen WANG (Tongxin xuebao)
The security model of the certificateless aggregate signature scheme with universal designated verifier was studied,and then a certificateless aggregate signature scheme with universal designated verifier using bilinear pairings was proposed.In the random oracle mode,based on the hardness of the computational Diffie-Hellman problem,the new scheme was proved to be secure against three attacks of certificateless aggregate signature scheme with universal designated verifier.Meanwhile,the scheme satisfies properties of strong designated verify and non-transferability.Furthermore,the length of final aggregate signature is equivalent as the length of signal user’s signature,it is more efficient than others because the pairing computation is fixed among public verifies and designed verifies.